Dick Bierman letter to Nicholas S. Halmi regarding bird sightings, February 11, 1978 - Bierman, Dicket al (1978)
Letter from Dick Bierman to Nicholas S. Halmi regarding bird sightings near Cherokee Iowa, February 11, 1978. Parts of the document mentioning sightings of Northern Shrikes, Common Redpoll, and Snow Buntings are underlined. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter, 1977-1978. Epson - sheet feed/flatbed